Atypical perianal and buttocks epidermal-dermal necrosis in Human Monkeypox. Histopathological study of the lesion in Peru - Terry Castellano, Luis E. (2023)
We report the histopathological study of a large, black, crusted lesion with symmetrical distribution in both buttocks and perineum, never described, in a man who has sex with men (MSM) and proctitis associated with Human Monkey Pox Virus (hMPXV) and HIV-AIDS infection never treated. A 39-year-old male, homosexual, HIV-AIDS without Highly Active Antiretroviral Therapy (HAART), was admitted to a hospital in Lima, Peru, with papulopustular lesions on the body and perianal area. Days later, a large, crusty, black lesion with a symmetrical distribution appeared on the buttocks and perineum. The tissue culture was negative. Wedge biopsy of the lesion showed typical MPXV cytopathogenics lesions in addition to fibrin micro thrombosis in the underlying papillary dermis. The histopathological findings of the scabby and black lesion are the classic ones described by Stagles, except for the phenomenon of fibrin micro thrombosis in the papillary dermis, a novel cytopathogenic effect of MPXV with clinical relevance (epidermal-dermal necrosis).